Addressing Environmental Challenges of Porphyrin Mixtures Obtained from Statistical Syntheses - Hölzel, Helen; Muth, Maximilian; Lungerich, Dominik; Jux, Norbert (Chemistry Methods, 2021)
Syntheses of complex molecular mixtures on the preparative scale are often challenging steps for chemists, which go hand in hand with expensive purification steps. Herein, the preparation and isolation of unsymmetrically substituted porphyrins, obtained from statistical reactions between two benzaldehydes, were investigated. Therefore, a semi-automated modular process was developed to lower the consumable costs, save time, and reduce waste production. We utilized a monomode microwave reactor equipped with an autosampler, and a medium pressure liquid chromatography (MPLC) flash purification device, equipped with a UV/Vis detector and a re-usable glass column packed with SiO2. With this method, it was possible to synthesize and purify several statistical porphyrin mixtures, while simultaneously reducing the environmental factor (E-factor) significantly, compared to conventionally performed porphyrin syntheses. Our approach shows that a sustainable investigation of academically relevant low-symmetrical porphyrins can be carried out feasibly, without sacrificing invested time.
CRIS-Team Scopus Importer:2024-12-16
Keywords: chromatography; E-factor; Porphyrin; statistical synthesis; sustainability